If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8q + 3b = 12 Reorder the terms: 3b + 8q = 12 Solving 3b + 8q = 12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8q' to each side of the equation. 3b + 8q + -8q = 12 + -8q Combine like terms: 8q + -8q = 0 3b + 0 = 12 + -8q 3b = 12 + -8q Divide each side by '3'. b = 4 + -2.666666667q Simplifying b = 4 + -2.666666667q
| 23x=136 | | D=-50m+500 | | 18m+4n=138 | | 5(4x+6)=-190 | | 2x-5=11+x | | 4*y=60 | | 10x+28=6x-28 | | 12y^3+1y^2-6y=0 | | -x-10=-6x+45 | | 0=-20x^2+320x-780 | | (A+7)(a-1)=20 | | 0.5x+0.2y=4.05 | | .5(x+5)=36 | | .5x=36+5 | | 5=4+i | | .5x+5=36 | | 12.00+0.15x=10.00+0.25x | | .5(x-5)=36 | | x=4x-24 | | .5a(x-5)=36 | | f(-3)=3x^2-x | | .5a+5=36 | | 3sinx-4sin^3x=1-2sin^2x | | .25x+5=36 | | .25(x+5)=36 | | .25(x-5)=36 | | .25x=36+5 | | 3(1-6x)=147 | | 7(1x+7)=77 | | -0.01x^2+0.26x+7.60=9.2 | | 2x+5+31=4x-10 | | 7x+2=6x+11 |